Participatory prioritization of climate-smart agriculture techniques: Case study of processes and outcomes from the Tra Hat Climate-Smart Village in Vietnam - Ngo Dang Phong; Tran Nhat Lam Duyen; Le Minh Duong; Wassmann, Reiner; Sander, Björn Ole (2019)
Participatory research allows groups and individuals to reflect and decide on their societal issues together. Such research was employed in Tra Hat Climate-Smart Village (CSV) in Vietnam to see if specific climate-smart agriculture (CSA) techniques could be adopted in the village. In line with the adoptability of CSA techniques, their scaling potential in the nearby areas of Tra Hat CSV was examined as well. Results showed that farmers deemed the CSA techniques related to rice production as priorities, which included laser land levelling, alternate wetting and drying, straw baler and rice root cutter, and Phosphorous fertilizer reduction, among others. Alongside CSA techniques on rice production, multiple crop and livestock practices were prioritized by the farmers due to their economic and environmental benefits. These CSA techniques could then be integrated into the “1M5R” or the “1Must-5Reductions” package, one of the current agricultural extension supports provided by the government. Gendered differences also emerged from the study, showing the preferred CSA techniques of male and female farmers and the factors that influenced them for their decisions. Regardless, they all believed that the CSA techniques they identified as priorities could increase incomes, ensure food security, and protect their environment. Results of this study exhibit the critical role of participation in empowering communities and the scaling potential of specific CSA techniques.